Bounded 3-Manifolds with Distance $n$ Heegaard Splittings (Communications in Mathematical Research, 2021)
We prove that for any integer $n ≥ 2$ and $g ≥ 2$, there are bounded3-manifolds admitting distance $n$, genus $g$ Heegaard splittings with any given boundaries.